Neighborhood disadvantage and general anesthesia utilization in cesarean delivery: a retrospective analysisAJOG Global Reports at a Glance - Andrea J. Ibarra, MD, MS; Hannah Campion, MD; Cecilia Canales, MD, MS; Brittany N. Burton; Alejandro Munoz, MD, PhD; Robert S. White, MD, MS; Runjia Li, MS; Goundappa K. Balasubramani, PhD; Janet M. Catov, PhD, MS (Elsevier, 2024)
Background: Neighborhood disadvantage, a social driver of health (SDOH), has been associated with adverse perinatal outcomes; yet little is known about its association with anesthetic choice. Objective: The purpose of this study is to assess the association of neighborhood disadvantage and anesthetic choice for cesarean deliveries. We hypothesize that people from the most disadvantaged neighborhoods are more likely to receive general anesthesia for cesarean deliveries compared to those from the most advantaged neighborhoods. Study design: This single-center retrospective cohort study identified index cesarean deliveries performed between 2008 and 2017. People were categorized into no, low, moderate, and high disadvantage neighborhood using the area deprivation index. The odds of receiving general anesthesia versus neuraxial anesthesia (epidural, spinal, or combined spinal-epidural) were compared using logistic regression models. Results: Of the 16,351 people with cesarean deliveries, 96.0% received neuraxial versus 4.0% general anesthesia. The rates of general anesthesia were 6.3%, 4.2%, 3.1%, and 2.4% for the high, moderate, low, and no disadvantage groups (P<.001), respectively. Indications for general anesthesia by obstetric indication were different by neighborhood disadvantage (P<.001), but no differences were observed by contraindications of neuraxial anesthesia (P=.091). Compared to the no disadvantage group, the high disadvantage group had higher odds of general anesthesia (aOR 2.0, 95% CI (1.5 to 2.7), P<.001). Results were unchanged after evaluating people in labor only. Conclusions: People from disadvantaged neighborhoods are more likely to receive general anesthesia for cesarean deliveries, even after considering clinical features. The general anesthesia rate is a meaningful benchmark in obstetric anesthesia that may contribute to disparities.